Bullous systemic lupus erythematosus a case report - Ali, Chowdhury Mohammad; Kamal, SM Bakhtiar; Khan, Md Mosaraf Hossain (Journal of Dhaka Medical College, 2013)
Bullous systemic lupus erythematosus (BSLE) is a rare but distinct disease, characterized by vesicobullous skin eruptions in systemic lupus erythematosus (SLE). It can arise either before or after a diagnosis of SLE has been established. BSLE is characterized by a dermatitis herpetiformis-like histology and an autoimmunity to type VII collagen. It must be differentiated from other autoimmune vesicobullous diseases such as epidermolysis bullosa acquisita, dermatitis herpetiformis, linear IgA disease, and bullous pemphigoid. A combination of clinical, histological, and immunofluorescence findings are necessary to establish a diagnosis of BSLE. We present a case of BSLE to illustrate and emphasize the need for an integrative diagnostic approach. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15691 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 90-92